2021
DOI: 10.1017/s0954579421000365
|View full text |Cite
|
Sign up to set email alerts
|

A network approach to dyslexia: Mapping the reading network

Abstract: Research on the etiology of dyslexia typically uses an approach based on a single core deficit, failing to understand how variations in combinations of factors contribute to reading development and how this combination relates to intervention outcome. To fill this gap, this study explored links between 28 cognitive, environmental, and demographic variables related to dyslexia by employing a network analysis using a large clinical database of 1,257 elementary school children. We found two highly connected subpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…The fourth and completely revised edition of the ZLT-II includes seven subtests. We included those five components of the ZLT-II which tap into key predictors of dyslexia (reading accuracy, reading speed, naming speed, and phonological short-term memory, see also Verwimp et al, 2021), but excluded two tasks that measure phonological awareness as previous studies found a ceiling effect for the age group of our study (e.g., Kormos et al, 2019; Landerl et al, 2013). The ZLT-II was administered and scored individually in face-to-face sessions with each child.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth and completely revised edition of the ZLT-II includes seven subtests. We included those five components of the ZLT-II which tap into key predictors of dyslexia (reading accuracy, reading speed, naming speed, and phonological short-term memory, see also Verwimp et al, 2021), but excluded two tasks that measure phonological awareness as previous studies found a ceiling effect for the age group of our study (e.g., Kormos et al, 2019; Landerl et al, 2013). The ZLT-II was administered and scored individually in face-to-face sessions with each child.…”
Section: Methodsmentioning
confidence: 99%
“…The fourth and completely revised edition of the ZLT-II includes seven subtests. We included those five components of the ZLT-II which tap into key predictors of dyslexia (reading accuracy, reading speed, naming speed, and phonological short-term memory, see also Verwimp et al, 2021), but excluded two tasks that measure phonological awareness as previous studies found a ceiling effect for the Learners listen to soundfile once while seeing the item(s) and being able to take notes (as in standard condiƟon) Learners then click 'next' to access the audio for self-pacing Learners now have control over soundfile and can pause and replay as they wish, without being able to see the items Once learners are ready to aƩempt answering the item(s), they click 'next' Learners now see them item(s) again and answer the item(s) by selecƟng the appropriate response(s). They then move on to the next soundfile and item(s).…”
Section: Methodsmentioning
confidence: 99%
“…Although our brain is not hardwired for reading, the vast majority of the population learns how to read relatively effortlessly. Previous studies have suggested that learning to read is a complex behavior that develops from dynamic interactions between multiple processes (Pennington, 2006; van Bergen et al, 2014; Verwimp et al, 2021), but these processes have commonly been studied in isolation. It, therefore, remains unclear how top‐down processes and subsequent consolidation contribute to the initial phases of reading acquisition.…”
Section: Learning To Readmentioning
confidence: 99%
“…One line of research conceptualizes multiple factors as variables located at different levels: typically, genetic, neurobiological, cognitive, behavioral [36,45,46]. As suggested by [46], this approach should probably be defined as multidimensional rather than multifactorial, since it observes the mutual interactions of factors that are not at the same logical level, but rather span over various dimensions that can generally be ordered in terms of the directions of causal relationships.…”
Section: Multiple-deficit Models Of Dd As a Non-unitary Conceptmentioning
confidence: 99%
“…As suggested by [46], this approach should probably be defined as multidimensional rather than multifactorial, since it observes the mutual interactions of factors that are not at the same logical level, but rather span over various dimensions that can generally be ordered in terms of the directions of causal relationships. Thus, several studies have searched for risk and protective factors at the genetic and environmental levels that could modulate the expression of other genetic or environmental factors on the cognitive and behavioral levels [45,[47][48][49][50]. Clearly, this approach is reasonable but also very ambitious, considering that the interactions of factors across levels are still poorly known and ill-defined.…”
Section: Multiple-deficit Models Of Dd As a Non-unitary Conceptmentioning
confidence: 99%